Physical exercise in adults with metabolic syndrome: a integrative review - Pivatto, Fernanda; Vicentini de Oliveira, Daniel; Pereira Marques, Izabela Vitória; Acencio, Fábio Ricardo; Degasperi Ieker, Ana Silvia (Arquivos do Mudi, 2025)
Introduction:Metabolic Syndrome is a condition marked by risk factors that raise the chances of cardiovascular disease and type 2 diabetes. Objective: This integrative review aimed to analyze the effects of physical exercise on adults with Metabolic Syndrome. Method: A literature search was conducted in Google Scholar, LILACS, MEDLINE, SciELO, and PubMed, applying specific inclusion criteria: randomized studies, adults aged 18–60, diagnosed with Metabolic Syndrome, published between 2009 and 2019, and from Latin American countries. Results: Of the 1,161 studies initially found, seven met the criteria. The results show that physical exercise plays a key role in reducing risk factors, with benefits including weight loss, lower blood pressure, increased HDL, reduced abdominal circumference, improved endothelial function, and reduced insulin resistance. Conclusion: Aerobic exercise, even in the short term, stands out as a crucial non-pharmacological intervention that enhances physical fitness and health outcomes in individuals with Metabolic Syndrome.